Lethal effect of filamentous algal blooms on Atlantic herring (Clupea harengus) eggs in the Baltic Sea. Issue 7 (5th May 2020) - von Nordheim, Lena; Kotterba, Paul; Moll, Dorothee; Polte, Patrick
Abstract: During this study, the effects of epiphytic filamentous algae on the survival of demersal spawned fish eggs were investigated in one of the most important spawning grounds of herring in the western Baltic Sea, which is subject to intense and ongoing eutrophication. In coastal marine ecosystems all over the world, eutrophication is a primary water quality issue, often resulting in mass developments of bloom‐forming algae. Macro‐algal blooms have immense ecological effects, as they alter the structure and the function of an ecosystem. Numerous fish species are affected, as they depend on those coastal areas for spawning and as juvenile habitats. A comparison of the survival of herring eggs on two natural spawning beds re‐vealed an immense impact of a filamentous algal bloom. The mortality rate reached nearly 100% in the area with massive occurrence of filamentous brown algae. Hypothesizing that the presence of filamentous algae facilitates herring egg mortality, field and laboratory experiments were conducted and revealed particular effects of distinct algal species. The survival rate of artificially spawned eggs on algal substrates and control substrates was compared. Whereas filamentous forms of the green alga Ulva intestinalis induced no immediate effect, significantly higher egg mortality was documented in experiments with the filamentous brown alga Pylaiella littoralis . Considering the ecological and economical importance of herring and other coastal spawners on the one hand and the persisting and increasing effects of eutrophication and climate change on the other hand, the results of our study clearly underpin the necessity to increase global efforts to reduce nutrient loads in coastal waters.